The Effect of Substitution Drill on Students' Vocabulary Mastery An Experimental Study at Yayasan Kubah Rahmatan Indonesia - Saefudin, Dery Purnama; Mulyadi, Mulyadi; Nurani, Siti (Universitas Muria Kudus, 2025)
The objectives of this research are to evaluate the effectiveness of the Substitution Drill technique in improving vocabulary mastery in English and its impact on active student participation at Yayasan Kubah Rahmatan Indonesia. This research is a quasi-experimental study with a pretest-posttest design without a control group. The sample of this research consists of 30 students from grades 2 to 6 with diverse ages and language abilities. The data were gathered by using a pretest and posttest to measure changes in vocabulary mastery, as well as observations to assess students' active participation in learning activities. The data were analyzed by comparing pretest and posttest scores and interpreting the observation results. The findings showed a significant improvement in vocabulary mastery, with the average score increasing from 60.2 on the pretest to 78.4 on the posttest (p 0.01). Additionally, students became more enthusiastic and active in using new vocabulary in sentence contexts. In conclusion, the Substitution Drill technique is effective in improving students' vocabulary mastery and can be implemented as an interesting and beneficial method for teaching English at Yayasan Kubah Rahmatan Indonesia.